Genetic characteristics of the Dreissena polymorpha population in Latvia (Lake Rāzna) as part of the European population - Morozova, Akeksandra; Shkute, Natalja (Archives of Biological Sciences, 2023)
Paper description: Dreissena polymorpha has spread widely throughout the territory of Latvia, negatively impacting biota. We examined the population genetic structure of this invasive species with microsatellites as a molecular marker. Levels of allelic diversity and mean expected heterozygosity were high for the investigated population. High genetic diversity was observed which enables species to adapt to new environments. These results contribute to the identification of effective management strategies for controlling polymorpha. Abstract: The zebra mussel Dreissena polymorpha is widely distributed in Europe. The expansion of zebra mussels has a negative impact on the native biota of lakes or rivers. Studies of the genetic structure of populations allow the identification of the current state of this invasive species in Latvia as a part of the European population. Despite the increasing importance of microsatellites in studies of population genetics, there is a lack of such data on D. polymorpha in Latvia. The present study investigates the genetic population structure of zebra mussels using six microsatellite loci as follows: DpolA6, Dpo260, Dpo272, Dpo101, Dpo221 and Dpo04 from Lake Rāzna. The microsatellite loci in the investigated population have a high polymorphism and number of alleles. Allelic diversity at all described loci was high, ranging from 4 to 20 alleles per locus. The mean observed heterozygosity was 0.58 and the mean expected heterozygosity was 0.70. A high genetic diversity enables species to adapt to changing environments.